Music as Equilibrant of Mood When Stressed as Perceived by Second Year Psychology Students: Toward a Guide in Stress Management Program (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Exams, assignments, school requirements, tour, school programs, projects, and reports are examples of activities that a typical student generally do at school to meet the vital part of being a student. These school loads occasionally make a student anxious and stressed if these activities are done all at once. This study utilized the normative descriptive method with quantitative research. The research subject of this study is composed of 50 2nd-year Psychology students. In the quantitative part, the researchers surveyed to get the profile of the respondents. The researchers also used a normative descriptive method with a survey questionnaire to interpret the results of the study, such as the factors that cause stress, the behavioral expression of the respondents, the effects of music, and the genres of music that help eliminate stress. Most of the respondents are females aged 19–20 years old. The factors that cause stress to the respondents included time management, financial problem, dirty environment, competition, etc. The behavior of the respondents under stress includes lack of sleep, staying up late, and overthinking. Listening to classical, instrumental, and Asian music helped the respondents lower their stress levels. These findings enabled the researchers to utilize a stress management program. Students should have a healthy environment free from dirt and noise pollution, which causes stress in studying. The teachers should provide interventions and other means of providing a good environment to students. The school administration should provide some equipment or materials for mental health. The school administration should also use psychological intervention in reducing stress, such as classical, instrumental, and Asian music. The school should implement the crafted guide to minimize stress to students, and future researchers should conduct further studies to verify the results of this study.
Keywords: stress, stress management, alleviate, accompaniment, curated, diversion, elevate, mood, nostalgia, unparallel